Composition dependence of the structural chemistry and magnetism of Ca2.5Sr0.5(Ga,Co)(1+x)Mn2-xO8 - Allix, M; Battle, P; Frampton, P; Rosseinsky, M; Ruiz-Bustos, R (2006)
Polycrystalline samples of bilayered brownmillerite-like Ca 2.5Sr0.5GaCo0.15Mn1.85O8 and Ca2.5Sr0.5Ga1.2Mn1.8O 8 have been prepared and characterised by magnetometry and neutron diffraction over a wide temperature range. The structural chemistry and magnetic properties are compared to those of Ca2.5Sr0.5GaMn 2O8. Ga enrichment has a significant effect on the former but not on the latter, whereas changes in both occur when paramagnetic Co 3+ cations enter the parent phase on the 4-coordinate sites. The coupling between the environment around the 4-coordinate cations and the transition to an antiferromagnetic ordered state that was observed in Ca 2.5Sr0.5GaMn2O8 is not apparent in the cation-substituted compositions, although both show long-range antiferromagnetic order at low temperatures. © 2005 Elsevier Inc. All rights reserved.